2010
DOI: 10.1371/currents.rrn1194
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cases associated with pandemic influenza A (H1N1) reported in Greece.

Abstract: Between 18 May 2009 and 3 May 2010, a total of 149 fatal cases associated with pandemic influenza A (H1N1) were reported in Greece. Detailed case-based epidemiological information was available for the large majority of fatal cases. The time distribution follows an epidemic curve with a peak in the beginning of December 2009 and a second peak one month later. This is similar to that of laboratory confirmed cases and influenza-like illness cases from our sentinel surveillance system, with two weeks delay. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 14 publications
4
21
2
1
Order By: Relevance
“…43,44 Previous reports have shown that radiologically confirmed pneumonia is associated with severe outcomes. 3,4,8,20,32 Although multivariate analysis did not reveal that pneumonia on admission was a significant clinical risk factor for a severe outcome in our study, it is noteworthy that 64% of subjects with 2009 H1N1 had infiltrates on x-rays at admission (92% for ICU subjects) compared with 17% of subjects presenting with an influenzalike illness, underlining its significance in complicating the confirmed cases requiring hospitalization.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…43,44 Previous reports have shown that radiologically confirmed pneumonia is associated with severe outcomes. 3,4,8,20,32 Although multivariate analysis did not reveal that pneumonia on admission was a significant clinical risk factor for a severe outcome in our study, it is noteworthy that 64% of subjects with 2009 H1N1 had infiltrates on x-rays at admission (92% for ICU subjects) compared with 17% of subjects presenting with an influenzalike illness, underlining its significance in complicating the confirmed cases requiring hospitalization.…”
Section: Discussioncontrasting
confidence: 65%
“…Among these cases, 294 were admitted to ICUs, and 149 died from causes related to 2009 influenza A (H1N1). [2][3][4][5][6][7] Since that period, influenza epidemics have resulted in an estimated 3-5 million cases of severe illness and 250,000 -500,000 deaths each year. 1,8,9 The risk of complications from influenza, including lower respiratory tract infection, hospital admissions, and death, depends on varying determinants such as age and type of comorbidity that may be present.…”
Section: Introductionmentioning
confidence: 99%
“…During the global 2009 H1N1 pandemic [A(H1N1)pdm09], there were significantly higher infection rates in children, and approximately 80% of deaths due to A(H1N1)pdm09 infection occurred in individuals aged < 65 years 1 . Although the clinical manifestations of A(H1N1)pdm09 and seasonal H1N1 infections were similar 2 , many severe and fatal cases of A(H1N1)pdm09 occurred not only in patients with underlying diseases but also in healthy children and young adults 3 , 4 . Some reports have shown that bronchial asthma was one of the most common underlying conditions in patients hospitalized with A(H1N1)pdm09 infection 5 , 6 .…”
Section: Introductionmentioning
confidence: 96%
“…The A(H1N1)pdm09 viral infection was considered a mild disease, similar to seasonal influenza. However, many severe and fatal cases were observed not only in the high-risk groups, but also among healthy children and young adults during the pandemic waves (Athanasiou et al, 2010; Reichert et al, 2010). …”
Section: A(h1n1)pdm09 Viral Infection and Asthmamentioning
confidence: 99%